Health Service Quality with Inpatient Satisfaction - Magfiroh Magfiroh; Antonius Rino Vanchapo; Abdul Karim; Guijiao Zou; Lie Jie; Cai Jixiong (Journal of World Future Medicine, Health and Nursing, 2023)
The quality of health services is health services that can satisfy every user of health services that is in sync with the level of satisfaction of the average population and the implementation is in accordance with professional standards and ethical codes. Service quality and patient satisfaction are the two most important things in hospital services. This literature review aims to determine the relationship between the quality of health services and the satisfaction of inpatients. This type of research is literature review research, the articles used were obtained from PUBMED and Google Scholar with articles published starting from 2018-2022. The number of journal articles was 8 articles analyzed. The results showed that there was a relationship between the quality of health services (asscurance, empathy, responsiveness, tangible and reliability) with inpatient satisfaction at the hospital. It can be concluded that satisfaction is a level of patient feeling that arises as a result of the service performance that is obtained after the patient compares it with what he expects. If the patient is dissatisfied with the nursing services provided, he will not seek the service or accept it, even though the service is available, practically obtainable and reachable.